2015
DOI: 10.1017/s0008423915000293
|View full text |Cite
|
Sign up to set email alerts
|

Research Note: A Profile of Ministerial Policy Staff in the Government of Canada

Abstract: Although ministerial political advisors are prominent and influential actors within the core executive in Canada and elsewhere, information is scarce with respect to their personal and professional backgrounds and career trajectory. This article uses recent survey data and publicly available biographical information to analyse the demographic composition of senior ministerial policy advisors within the Government of Canada. It finds that, while ministerial policy staffers are young and politically committed, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 15 publications
0
12
0
2
Order By: Relevance
“…This is consistent with Eichbaum and Shaw who characterized advisors “principally as ministers' agents, rather than as policy entrepreneurs” (2011: 591). While some political advisors may have subject matter expertise, most are younger and less experienced than their senior public service interlocutors (Wilson ) and can seldom match the expertise of officials. Regardless of personal background, however, their job is not to compete with departmental technical expertise but, as described below, to complement it with political analysis.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is consistent with Eichbaum and Shaw who characterized advisors “principally as ministers' agents, rather than as policy entrepreneurs” (2011: 591). While some political advisors may have subject matter expertise, most are younger and less experienced than their senior public service interlocutors (Wilson ) and can seldom match the expertise of officials. Regardless of personal background, however, their job is not to compete with departmental technical expertise but, as described below, to complement it with political analysis.…”
Section: Methodsmentioning
confidence: 99%
“…While a growing corpus of international research provides a high‐level portrait of the activities of political policy staffers, generalizations are inadequate in two important respects. First, they tend to present ministerial advisors as an undifferentiated category; this is problematic since they are growing not only in number but specialization (Tiernan ; Wilson ). Second, advisors' day‐to‐day activity is “contextually specific” (Shaw and Eichbaum : 586), varying from country to country and even from government to government (Eichbaum and Shaw ).…”
Section: Introductionmentioning
confidence: 99%
“…Dva istraživanja pokazala su da među savjetnicima dominiraju muškarci -u Irskoj ih je bilo 71,4%, a na Novom Zelandu 65,6% (Connaughton, 2010, Eichbaum & Shaw, 2007. Također, vidljiv je trend angažiranja sve mlađih savjetnika (Halligan, 2013) koji su spremni dokazivati se radi napredovanja u karijeri pa stoga ne čudi da je polovica savjetnika u Kanadi u tridesetim godinama, a dodatno je 21% i mlađih (Wilson, 2015).…”
Section: Promijenjena Uloga Policy Savjetaunclassified
“…In May 2007 only 44 public servants were employed in Canadian ministers' offices as exempt staff (Aucoin , p. 69). A survey of 64 senior policy advisers working for Canadian ministers found that only three had previously worked in the public service (Wilson ) . The subgroup of ministerial staff who are public servants is larger in Australia than in Canada.…”
Section: The Employment Of Public Servants In Ministers' Officesmentioning
confidence: 99%